Impact of spectral filtering on pulse breaking-up and noise-like pulse generation in all-normal dispersion fiber lasers - Xu, Runqin; Xu, Fanjiang; Song, Yanrong; Duan, Lei; Song, Yunbo; Tan, Shudan; Liu, Zhaohui (Optics express, 2020)
Based on mathematic simulations, the impact of spectral filtering on pulse breaking up and noise-like pulse generation in all-normal-dispersion fiber lasers are investigated. Three types of spectrum filters are employed in the simulations, which have a Gaussian-shaped profile, super-Gaussian-shaped profile, and sinusoidal-shaped profile, respectively. With the Gaussian-shaped filter, the pulse breaking-up process is discussed. The super-Gaussian-shaped filter and the sinusoidal-shaped filter have two different formation mechanisms for noise-like pulses and are revealed. In addition, with the sinusoidal-shaped filter, dissipative solitons of different central wavelengths are achieved.